Discrete resource allocation to groups of customers - Tiešis, Vytautas (Lietuvos matematikos rinkinys, 2005)
The paper deals with the non-homogeny discrete resource allocation to groups of customers with non-linear profit functions. The fast hierarchical greedy algorithms are presented and investigated. The exact upper boundwas found for complexity of the algorithm. The experiments prove the advantage of the modification of the algorithm.